Corpo e saúde na antroposofia: bildung como cura - Bastos, Raquel Litterio de [UNIFESP] (2016)
Anthroposophy is a neo romantic spiritual science of the early twentieth century, developed by Austrian philosopher and esoteric Rudolf Steiner, Switzerland. Anthroposophy contributes in various areas of knowledge with their spiritual empiricism imputed Goethe's phenomenology, scientist and poet of German Romanticism. Between the areas that acts are organic architecture, biodynamic agriculture, Waldorf pedagogy and anthroposophic medicine, considered a medical rationality in the SUS and amplifying biomedicine. In Brazil, Anthroposophy was installed in the 1930s, but its expansion occurred in the 1960s, when he inaugurated the first medical clinic – Clinic Tobias, in Santo Amaro – Capital – and the first farm biodynamic in São Paulo – the current Demetria district in the city of Botucatu – both pioneers in Latin America and outside Europe. The objective of the research was to comprise the concept of healing in anthroposophy and its relation to the word-concept Bildung as a therapeutic motto. To do this research adopted a qualitative methodology, conducted through an ethnography, conducting participant observation procedures, interviews and accompaniment the daily life of interlocutors described densely. The research began in 2012, first in the Anthroposophical Society courses and then the participation of body, soul and spirit therapies in Clinical Tobias (in Tobias Branch); in 2013 ethnography was performed in the rural district of Demetria, following the daily life of its residents (in Jatoba Branch); and in 2014 the survey was conducted in Switzerland, in Lausanne (in Branch Christian Rose Croix). The search results show a close relationship between the concept of healing and the elements that make the German romantic medicine: science, morality and aesthetics. Healing in anthroposophy is in search for a Bildung, as well as the European Bildung works as legitimizing motto for healing, especially in middle-class intellectualized in São Paulo. The way to go necessarily need to present an epic aesthetics in face of adversity. For this, the Anthroposophists extol an emotional grammar, where courage, inspired by the archangel Michael and the mythological willpower are the great inspiration. However, the aesthetic values of the German Bildung have adapted to Brazilian culture, transforming healing.